Предмет: Алгебра,
автор: Аноним
Упростите выражение
3х²-(3х-1)(х+2)
и найдите его значение при х=-3
Ответы
Автор ответа:
0
3x²-3x²-6x+x+2=-5x+2
x=-3 -5*(-3)+2=15+2=17
x=-3 -5*(-3)+2=15+2=17
Автор ответа:
0
Благодарю)
Автор ответа:
0
3x²-(3x-1)*(x+2)=3x²-(3x²+5x-2)=3x²-3x²-5x+2=-5x+2
При x=-3
15+2=17
Ответ:17.
При x=-3
15+2=17
Ответ:17.
Автор ответа:
0
Благодарю))
Похожие вопросы
Предмет: Литература,
автор: alexgala000o
Предмет: Русский язык,
автор: Аноним
Предмет: Алгебра,
автор: vinorabut
Предмет: Математика,
автор: рекн
Предмет: Химия,
автор: іннаqwe